A CRITICAL REVIEW OF AUTOMATED PHOTOGRAMMETRIC PROCESSING OF LARGE DATASETS - F. Remondino; E. Nocerino; I. Toschi; F. Menna (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2017)
The paper reports some comparisons between commercial software able to automatically process image datasets for 3D reconstruction purposes. The main aspects investigated in the work are the capability to correctly orient large sets of image of complex environments, the metric quality of the results, replicability and redundancy. Different datasets are employed, each one featuring a diverse number of images, GSDs at cm and mm resolutions, and ground truth information to perform statistical analyses of the 3D results. A summary of (photogrammetric) terms is also provided, in order to provide rigorous terms of reference for comparisons and critical analyses.